Islands at the Crossroads : Migration, Seafaring, and Interaction in the Caribbean. - Hauser, Mark W.; Armstrong, Douglas V.; Berman, Mary Jane; Boomert, Arie, 1946-; Bright, Alistair J.; Callaghan, R. T. (Richard T.); Curet, L. Antonio, 1960-; Hofman, Corinne L., 1959-; Hoogland, Menno Lambertus Pieter, 1954-; Kelly, Kenneth Goodley, 1962-; Knippenberg, Sebastiaan, 1970-; Newquist, Ingrid M.; et al. (Caribbean archaeology and ethnohistory., 2011)
Islands at the Crossroads: Migration, Seafaring, and Interaction in the Caribbean (Caribbean Archaeology and Ethnohistory).